1986
DOI: 10.3109/10641968609046595
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Behaviour and Control in Turner Syndrome

Abstract: TS patients show high frequency of hypertension in pediatric age. Estrogen therapy is an outbreaking and worsening factor. An estrogen independent role of the renin-angiotensin-aldosterone system in the pathogenesis of TS hypertension is still uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…Small vessel renovascular disease has been proposed as a possible explanation, given the elevated renin activity which may be found before oestrogen therapy is instituted. Karyotype does not appear to influence the prevalence of hypertension, which may be underestimated without the use of age-related normal ranges [3, 62, 82]. Hypertension is exacerbated by ethinyl oestradiol but not by natural oestrogens or growth hormone [31, 83].…”
Section: Clinical Manifestations Of Turner Syndrome In Adultsmentioning
confidence: 99%
“…Small vessel renovascular disease has been proposed as a possible explanation, given the elevated renin activity which may be found before oestrogen therapy is instituted. Karyotype does not appear to influence the prevalence of hypertension, which may be underestimated without the use of age-related normal ranges [3, 62, 82]. Hypertension is exacerbated by ethinyl oestradiol but not by natural oestrogens or growth hormone [31, 83].…”
Section: Clinical Manifestations Of Turner Syndrome In Adultsmentioning
confidence: 99%
“…Its etiology is considered multifactorial, while possible mechanisms include high levels of plasma renin activity, obesity, aortic coarctation, and renal vascular abnormality [8,13,14]. In this report, the patient had untreated hypertension and associated cerebral hemorrhage, but her primary physician had not recognized hypertension during her routine visits.…”
Section: Discussionmentioning
confidence: 94%
“…The contribution of the RAA axis in the pathogenesis of hypertension remains uncertain. In younger Turner syndrome girls, increased levels of plasma renin activity are found to be associated with hypertension and abnormal response to angiotensin-converting enzyme (ACE) inhibition in one study [34], but this relationship could not be confirmed in another [51]. The sympathetic nervous system -an important actor in blood pressure regulation [52] -is over-activated in Turner syndrome [35,53] and leads to both increased blood pressure and a higher heart rate.…”
Section: Cause Of Hypertension In Turner Syndromementioning
confidence: 94%